RESPON CIVITAS AKADEMIKA IAIN TERNATE TERHADAP PERBANKAN SYARIAH DI KOTA TERNATE - Nirwan Umasugi (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2022)
The aim of this study was to identify the significant relationship between perception and behavior, the gap in the behavior of the IAIN Ternate academic community towards Islamic banking to become partners in products and services for the socialization and development of Islamic banks, and to transform the behavior of the IAIN Ternate academic community towards Islamic banking. This study uses a quantitative descriptive analysis method and is a survey study. From the entire academic community of IAIN Ternate, samples were taken using a random sampling technique. The study's findings demonstrate that the academic community of IAIN Ternate bases its decision to associate with Islamic banks primarily on rationalist and ideological conceptions, with considerations based on economic perceptions accounting for the remainder. The academic community at IAIN Ternate, however, does not behave in a way that is consistent with explicitly religious beliefs; rather, it is motivated by economic perceptions, which are in turn influenced by elements such as comfort, safety, and satisfaction as well as speculative actions. Because respondents' comments suggested a favorable attitude toward sharia banking, the study's findings also suggest that the goods and services employed to build sharia banks in Ternate City had considerable potential.Keywords: Reaction; Academic Community; Sharia Banking.